AK{NAUCHE, PERSONHOOD AND SOCIAL ORDER IN CONTEMPORARY IGBO CULTURE (2017)
Ak[nauche, an ontological and intelligent component of the human person capable of mediating and unifying the individual’s facets of existence, is central in maintaining social order in Igbo culture. Existing studies have addressed the idea of ak[nauche mainly from scientific and aesthetic perspectives, without adequate analysis of the concept in relation to the unity of the individual as a being of many parts, significant to the attainment of social order. This study, therefore, investigates ak[nauche with a view to identifying the ontological roles it plays in mediating between the individual and the community in ensuring social order. The study adopted Strawson’s theory on persons. Six relevant texts in Metaphysics; Descartes’ Meditations on First Philosophy (MFP), Collins’ Selfless Person (SP), Kim’s Supervenience and Mind (SM). Eight texts in African Philosophy, such as Mbiti’s African Religions and Philosophy ARP). Menkiti’s On the Normative Conception of a Person (NCP), Ikuenobe’s The Idea of Personhood in Chinua Achebe‘s Things Fall Apart (CATFA) and Animalu’s Ucheakolam: A way of Life in Modern Scientific Age (WLMSA), were purposively selected. Hence they addressed the issues of ak[nauche, personhood and social order. Conceptual analysis and reconstruction were deployed. Texts in Metaphysics reveal that human persons are in control of their well-being, do not consider the community as very significant in their explanations, and under-explore the connection between a person and the community (MFP and SM). Texts in African Philosophy show that the individual is bound to behave in certain ways laid down by the community, thereby inhibiting complete individual autonomy (ARP, NCP and CATFA). Igbo proverbs like, nwata kw[zie aka, o soro okenye, rie nri (outstanding achievement is acknowledged and rewarded) not only affirms that ak[nauche is paramount in a person’s relationships in the community, but also emphasises a person’s creativity (WLMSA). Critical reflection reveals that the person is creatively intelligent and that the human will is autonomous because each individual has ak[nauche which supervenes actions and thoughts in a way that enhances social order. The Igbo proverb, eruru si na [ bu uche[ma ka ha jiri t[pu osisi ngw[, ma na, otu-otu ka ha bi (Though we live individually, it is in harmony that we accomplish great feats), emphasises the synchronisation of personal and communal worth in achieving social order. Ak[nauche, an ontological component of a person, demonstrates that the human person is both a metaphysical and social being with creative intelligence. Therefore, ak[nauche in Igbo culture plays both creative and mediating roles in the relationship between the individual and the community in which social order is guaranteed